Declaration - + Józef Michalik; + Jan Martyniak; + Sviatoslav Shevchuk; + Mieczysław Mokrzycki (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2013)
Declaration of the Major Archbishop Sviatoslav Shevchuk, the Kiev-Halicz Metropolitan of the Ukrainian Greek-Catholic Church, Archbishop Metropolitan of Przemyśl of the Latins Józef Michalik, the President of Polish Bishops Conference, Archbishop Metropolitan of Lviv of the Latins Mieczysław Mokrzycki, the President of Roman-Catholic Ukrainian Bishops Conference, Archbishop Metropolitan of Przemyśl-Warsaw of the Byzantine-Ukrainian Church Jan Martyniak